E-145 Collateral patterns in large vessel occlusion stroke and outcomes after endovascular thrombectomy. (23rd July 2022) - Regenhardt, R; Lev, M; He, J; Dmytriw, A; Vranic, J; Rabinov, J; Stapleton, C; Patel, A; Singhal, A; Gonzalez, G
Abstract : Introduction: Endovascular thrombectomy (EVT) has revolutionized large vessel occlusion (LVO) stroke care. However, treatment decisions and prognostication are challenging when advanced imaging is unavailable. We sought to determine the relationship of presentation simple CTA collateral patterns and outcomes after EVT. Methods: We identified patients with anterior circulation LVO who underwent guideline-based EVT from 2019 to 2020 at a single referral center. Inclusion criteria were available CTA for retrospective review and 90-day modified Rankin Scale (mRS) score. Arterial phase CTA collaterals at presentation were categorized as malignant, other, or symmetric. Results: Among 74 patients, the median age was 75 (IQR 58–82), and 49% were female. Collaterals were symmetric (36%), malignant (24%), or other (39%). Comparing collateral patterns, there were no differences in demographics, risk factors, time from last known well, thrombolysis treatment, TICI 2b-3 reperfusion, or intracerebral hemorrhage. Median NIHSS was 18 (14–23) for malignant, 19 (12–22) for other, and 11 (8–18) for symmetric (p=0.02). Intracranial ICA occlusions were present in 28% of malignant, 3% of other, and 11% of symmetric (p=0.04). Ninety-day mRS ≤2 was achieved in 17% of malignant, 38% of other, and 67% of symmetric. Collateral pattern was an independent determinant of 90-day mRS ≤2 (aOR=6.62, 95%CI=2.24, 19.53; p=0.001) in a multivariable model controlling for age, NIHSS, baseline mRS ≥3, thrombolysis, occlusion location, and TICI 2b-3 reperfusion. Conclusions: Collateral pattern is a robust determinant of 90-day outcomes after EVT. It may help guide EVT decisions in the delayed window, especially when there are delays to treatment such as those related to patient transfer. Further prospective studies are needed to evaluate the role of collateral pattern in treatment decisions and prognostication. Disclosures: R. Regenhardt: None. M. Lev: None. J. He: None. A. Dmytriw: None. J. Vranic: None. J. Rabinov: None. C. Stapleton: None. A. Patel: None. A. Singhal: None. G. Gonzalez: None.